A Hollow and Compressible 3D Photothermal Evaporator for Highly Efficient Solar Steam Generation without Energy Loss. Issue 5 (11th March 2021) - Gao, Ting; Wu, Xuan; Wang, Yida; Owens, Gary; Xu, Haolan
Abstract : Solar steam generation offers a sustainable strategy to mitigate global clean water scarcity. To this end, 3D photothermal evaporators have attracted increasing research interest since they can significantly improve both evaporation rate and energy efficiency. However, compared to the 2D evaporators, the 3D ones consume more raw materials and occupy more storage space, which limits their applications for practical portable solar steam generation. To address this issue, a 3D hollow and compressible photothermal evaporator is designed and fabricated which can be compressed to less than one third of its original volume, thus enabling easier transport and storage. Moreover, under 1.0 sun illumination, all evaporation surfaces of this 3D evaporator are lower in temperatures than the surrounding environment, thus providing the unique advantage of zero energy loss to the environment during solar evaporation. Due to the all‐cold evaporation surfaces, during solar evaporation, the evaporator is able to harvest massive energy from both the surrounding air and bulk water, delivering an extremely high evaporation rate of up to 7.6 kg m −2  h −1 under 1.0 sun irradiation. Furthermore, seawater desalination tests demonstrate that the device has great potential for portable solar thermal desalination by delivering clean water with a salinity well below 50 ppb. Abstract : A hollow and compressible photothermal evaporator is designed and fabricated to realize portable solar steam generation without any energy loss. An extremely high evaporation rate of 7.6 kg m −2  h −1 with a corresponding energy efficiency far beyond the theoretical limit is achieved. The evaporator can be compressed for easy storage.